Annexin A1 Promotes Reparative Angiogenesis and Ameliorates Neuronal Injury in Ischemic Retinopathy. (4th May 2022) - Hui, Qiaoyan; Zheng, Fengwei; Qin, Li; Pei, Cheng
Abstract: Purpose: Retinal ischemia is the main reason for vision threatening. Inflammation and aberrant angiogenesis play an important role in the pathogenesis of ischemia. Annexin A1 (ANXA1) is an endogenous protein modulating anti-inflammatory processes, and its therapeutic potential has been reported in a range of inflammatory diseases. However, the effect of ANXA1 on ischemic retinal injury has not been examined. Methods: Expression of ANXA1 was assessed by real-time PCR and western blotting, and location of ANXA1 was evaluated by immunofluorescence staining in retina of OIR. The activation of ANXA1 was assayed in HRECs after hypoxia stimuli. The effect of ANXA1 on vascularization of OIR mouse through quantification vaso-obliteration (VO) and neovascularization (NV), as well as expression of relevant angiogenic factors and inflammatory cytokines was compared between wild type and ANXA1 deficiency mice. We also investigated the effect of ANXA1 on retinal neuronal degeneration as measured by electroretinography (ERG) and OCT. Results: In retinas of OIR, the expression of ANXA1 significantly increased and located in inner retinal layers. ANXA1 was induced in HRECs after hypoxic stimuli. Furthermore, ANXA1 deficiency increased pro-angiogenic and pro-inflammatory cytokines. Ablation of ANXA1 suppressed aortic outgrowth and retinal reparative revascularization and promoted pathological NV to exacerbate retinal dysfunction after ischemia injury. Conclusions: ANXA1 inhibits angiogenic and inhibits pro-inflammatory cytokines and promotes reparative angiogenesis, thus exhibits neuronal protective function in ischemic retinopathy.